Village Midwives’ Experiences with Maternal Emergency Management and Digital Health Systems: A Phenomenological Study in Rural Indonesia - Margaretha, Sumarti Endah Purnamaningsih Maria; Urrahman, Dhiya; Chrisnawati; Marwanta, Y. Yohakim; Baiquni, Fahmi (Journal of Applied Nursing and Health, 2026)
Background: Maternal and neonatal mortality remain significant challenges in low- and middle-income countries, particularly in rural Indonesia, where village midwives serve as the first responders to obstetric emergencies. Despite numerous digital health initiatives, fragmented systems and poor usability often hinder timely emergency management. This study aimed to explore the lived experiences, challenges, and expectations of community midwives in designing an effective maternal–neonatal emergency digital application in Tanah Laut District, South Kalimantan, Indonesia. Methods: This qualitative study employed a Husserlian descriptive phenomenological approach. Ten active village midwives were recruited through purposive sampling; inclusion required at least one year of experience, while those unable to attend or refusing participation were excluded. Data were collected in August 2024 through a focus group discussion (FGD) lasting 120 minutes. Data were analyzed using Colai zzi’s phenomenological analysis method, and reporting followed the COREQ guideline. Results: Five interrelated themes emerged: (1) Maternal emergencies as multidimensional crises, (2) Informal communication as the real emergency network, (3) Fragmented and burdensome reporting systems, (4) Digital and infrastructural barriers in rural practice, and (5) Expectations for an integrated, user-friendly digital solution. These themes progress conceptually from the initial crisis experience, through the mobilization of informal networks due to systemic barriers, culminating in user-driven expectations for digital design. Conclusion: The study highlights midwives’ resilience amid digital fragmentation. Policymakers and developers should adopt participatory co-design approaches involving midwives to ensure the usability and sustainability of maternal emergency digital systems